Application of intuitionistic fuzzy numbers in SWOT analysis. (2018) - Roghanian, Emad; Ghorbani, Baharak; Alipour, Mohammad
Strategic studies are of high importance in every business administration. Some of them, like strengths, weaknesses, opportunities, threats (SWOT), can be used widely. However, uncertainty is always considered as a major obstacle for extracting strategies from these techniques. On the other hand, introduction of fuzzy logic facilitates the connection between real world managerial problems and deterministic mathematics. This paper thus focused on vague characteristic of the data used in SWOT analysis, and tried to solve it by utilisation of the intuitionistic fuzzy numbers (IFN), as a transformation which enables the outcome of this procedure to be identified more explicitly.